Insulin secretion in monosodium glutamate (MSG) obese rats submitted to aerobic exercise training - De Souza, Claudio Teodoro [UNESP]; Nunes, Wilton Marlindo Santana [UNESP]; Gobatto, Claudio Alexandre [UNESP]; De Mello, Maria Alice Rostom [UNESP] (My University, 2003)
The present study was designed to evaluate the effects of aerobic exercise training on glucose tolerance and insulin secretion of obese male Wistar rats (monosodium glutamate [MSG] administration, 4mg/g-body weight, each other day, from birth to the 14th day). Fourteen weeks after the drug administration, the rats were separated into two groups: MSG-S (sedentary) and MSG-T (T = swimming, 1 h/day, 5 days/week, with an overload of 5% body weight for 10 weeks). Rats of the same age and strain injected with saline were used as control (C) and subdivided into two groups: C-S and C-T. Insulin and glucose responses during an oral glucose tolerance test (GTT) were evaluated by the estimation of the total areas under serum insulin (AI) and glucose (AG) curves. Glucose-induced insulin secretion by isolated pancreatic islets was also evaluated. MSG-S rats showed higher AI than C-rats while MSG-T rats presented lower AI than MSG-S rats. No differences in AG were observed among the 4 groups. Pancreatic islets from MSG-rats showed higher insulin secretion in response to low (2.8) and moderate (8.3 mM) concentrations of glucose than those from their control counterparts and no differences were observed between MSG-S and MSG-T rats. These results provide evidences that the hyperinsulinemia at low or moderate glucose concentrations observed in MSG-obese rats is, at least in part, a consequence of direct hypersecretion of the B cells and that chronic aerobic exercise is able to partially counteract the hyperinsulinemic state of these animals without disrupting glucose homeostasis.
Keywords: glucose; glutamate sodium; insulin; sodium chloride; aerobic metabolism; age distribution; animal cell; animal experiment; animal tissue; B lymphocyte; body weight; controlled study; exercise; female; glucose homeostasis; glucose tolerance; insulin blood level; insulin release; insulin response; male; nonhuman; obesity; oral glucose tolerance test; pancreas islet; physical activity; rat; strain difference; swimming; Animals; Blood Glucose; Body Weight; Fats; Female; Glucose; Glucose Tolerance Test; Insulin; Lactic Acid; Male; Obesity; Pancreas; Physical Conditioning, Animal; Rats; Rats, Wistar; Sodium Glutamate; Animalia; Rattus norvegicus